Batasan keluar rumah bagi wanita ’iddah wafat perspektif maslahah mursalah - Wardah, Rahmanialfi (Maliki Interdisciplinary Journal, 2024)
Women who are in the period of iddah (women who have recently lost their husbands) are not allowed to leave their homes unless it is an emergency. This was agreed upon by four Madzhab fiqh scholars. Experts differ regarding the timing and limits of the curfew for women after the Iddah period. The aim of the researchers was to investigate the time and limits within which women are prohibited from leaving their homes according to four schools of thought. The method used is descriptive analysis using inductive analysis techniques. The study found that in Idda, women are not allowed to leave the house to die unless it is an emergency, and are allowed to go out in the morning when performing the Hajj. At night, it is only allowed in case of emergencies or emergencies. According to Hajiya and Darriya, limiting women’s permission to leave the house for the sake of death is in the interests of other people and does not conflict with the principle of maslaha mursala.